Gambaran Karakteristik Kanker Payudara - Eneng Mira; Maya Tejasari; Listya Hanum Siswanti (Bandung Conference Series: Medical Science, 2024)
Abstract. The most common malignant disease in women is breast cancer. In the world the number of breast cancer sufferers has reached 2.3 million. The occurrence of breast cancer can be caused by several risks, including age, parity status, history of breastfeeding and use of hormonal contraception. This study aims to determine the characteristics of breast cancer patients. This research used a retrospective descriptive method which took place at Al-Ihsan Regional Hospital with 182 research subjects. Data was obtained from secondary data from medical records in the form of age characteristics, breastfeeding history, parity status and use of hormonal contraceptives. The results of the research show that the majority of breast cancer patients at Al-Ihsan Regional Hospital in 2022 are in the 46-55 year age group, namely 70 people (38.4%), 161 people have a history of breastfeeding (88.4%), parity status is mostly 2 –3 children totaling 132 people (72.5%) and using hormonal contraception as many as 155 people (85.2%). This is related to the high levels of the hormones estrogen and progesterone which influence the risk of breast cancer, thus inhibiting the tumor suppressor genes BRCA1 and BRCA2 which causes breast gland cell proliferation to increase. ​Abstrak. Penyakit keganasan terbanyak pada wanita adalah kanker payudara. Di dunia jumlah penderita kanker payudara mencapai angka 2,3 juta. Terjadinya kanker payudara dapat disebakan oleh beberapa risiko, diantaranya adalah usia, status paritas, riwayat menyusui dan penggunaan kontrasepsi hormonal. Penelitian ini bertujuan untuk mengetahui karakteristik pasien kanker payudara. Penelitian ini menggunakan metode deskriptif retrospektif yang bertempat di RSUD Al-Ihsan dengan Subjek penelitian sebanyak 182 orang. Data diperoleh dari data sekunder rekam medis berupa karakteristik usia, riwayat menyusui, status paritas dan penggunaan kontrsepsi hormonal. Hasil penelitian menunjukan mayoritas pasien kanker payudara di RSUD Al-Ihsan tahun 2022 pada kelompok usia 46-55 tahun yaitu sebanyak 70 orang (38,4%), riwayat menyusui sebanyak 161 orang (88,4%), status paritas sebagian besar mempunyai 2–3 anak sebanyak 132 orang (72,5%) dan memakai kontrasepsi hormonal sebanyak 155 orang (85,2%). Hal tersebut berkaitan dengan tingginya hormon estrogen dan progesteron yang berpengaruh terhadap risiko terjadinya kanker payudara, sehingga meng-inhibisi tumor supresor gen BRCA1 dan BRCA2 yang menyebakan proliferasi sel kelenjar payudara meningkat.